2015
DOI: 10.1111/prd.12117
|View full text |Cite
|
Sign up to set email alerts
|

Salivary cytokines as biomarkers of periodontal diseases

Abstract: Research into biomarkers of periodontitis is driven by mainly three targets: to identify 'at risk' patients before periodontal tissue destruction occurs; to determine disease activity and progression; and to build up our understanding of this complex disease with the purpose of finding new therapeutic targets. Whilst blood and gingival crevicular fluid were previously the biological samples of choice, saliva has recently gained more attention as a readily accessible oral fluid which has a mediator profile simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
108
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(124 citation statements)
references
References 114 publications
7
108
0
1
Order By: Relevance
“…The higher levels of salivary CRP are not surprising given that two thirds of the sample (68.7%) had visible inflammation in the mouth, which has been shown to increase salivary levels of CRP and other inflammatory biomarkers (Al Moharib et al, 2014). On the other hand, in a systematic review, researchers pointed out that there have been conflicting results with regard to a link between salivary IL-6 and periodontal disease: Some have found higher rates of IL-6 with periodontal disease and others have not (Jaedicke, Preshaw, & Taylor, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The higher levels of salivary CRP are not surprising given that two thirds of the sample (68.7%) had visible inflammation in the mouth, which has been shown to increase salivary levels of CRP and other inflammatory biomarkers (Al Moharib et al, 2014). On the other hand, in a systematic review, researchers pointed out that there have been conflicting results with regard to a link between salivary IL-6 and periodontal disease: Some have found higher rates of IL-6 with periodontal disease and others have not (Jaedicke, Preshaw, & Taylor, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…GCF collection is a minimally invasive procedure rather than gingival biopsies. It reflects the activity of individual crevicular sites rather than whole‐mouth inflammatory status as with saliva analysis 36 . A study by Guentsch et al 37 .…”
Section: Discussionmentioning
confidence: 99%
“…In the course of periodontitis, bacterial-induced osteoblast apoptosis may be a major contributor to bone loss. A number of studies have revealed that LPS is present in plaque, saliva, gingival crevicular fluid, inflammatory cavities and diseased cementum, with high toxicity to periodontal tissues (38)(39)(40). In addition, a previous study suggested that during alveolar bone resorption and periodontitis, bacteria do not directly invade gingival tissue; instead, the destruction of gingival tissue may be mediated by LPS cytotoxicity in the gingival crevice (37).…”
Section: Discussionmentioning
confidence: 99%